Expression, Purification, and Characterization of Cu/ZnSOD from Panax Ginseng - Ding, Dayong (Molecules, 2014)
Superoxide dismutase (SOD) has a strong antioxidant effect, but the traditional SOD extraction method is not the most efficient method of SOD amplification. In this study, we report the cloning of the Cu/ZnSOD gene from Panax ginseng into a temperature-regulated expression plasmid, pBV220. Cu/ZnSOD inclusion bodies were expressed in E. coli at a high level. Then, the inclusion bodies were purified by ion-exchange chromatography and molecular sieve chromatography. Finally, we obtained stable SOD in the bacterial broth, with a protein content of 965 mg/L and enzyme specific activity of 9389.96 U/mg. These results provide a foundation for future studies on the antioxidant mechanisms of ginseng and the development and application of ginseng Cu/ZnSOD.